3D Modelling and Dimensional Measurement of a Car using a Low-Cost Digital Camera - Setan, Halim; Tiong, Andrew Chiew Sien (ARSRIN, Thailand, 2001)
The development of digital technology in close range photogrammetry has many potential applications in industrial measurement.This study focuses on the applications of a low-cost digital camera (KodakDC210SP) and Photo Modeler Pro3.1 software for 30 modeling and dimensional measurement of a car.The resulted30 model of the car can be exported to other formats, such as AutoCad. For verification, the measurement obtained was compared with tape and intersection measurement. The results show differences of 1-7mm,indicating the suitability of the low-cost photogrammetric systems for applications requiring an accuracy of a few millimeter: